1996
DOI: 10.1002/(sici)1096-9861(19960101)364:1<121::aid-cne11>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Cytoarchitectural distribution of calcium binding proteins in midbrain dopaminergic regions of rats and humans

Abstract: The present study compares the distribution of three calcium binding proteins, calbindin-D28k, calretinin, and parvalbumin, in the midbrain tegmentum of rats and humans. In order to compare the distributions of these proteins directly, the cytoarchitecture of this region was evaluated by using immunohistochemistry for tyrosine hydroxylase and substance P in serial sections in both transverse and horizontal planes. There was a high degree of homology in the cytoarchitecture of the three main dopaminergic region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
110
0
4

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 98 publications
15
110
0
4
Order By: Relevance
“…When control tissues obtained from a cynomolgus embryo and an adult animal were analyzed, both showed that the substantia nigra pars compacta (SNc) was strongly positive for GIRK2 and FOXA2 and weakly positive for calbindin, while the ventral tegmental area (VTA) was weakly positive for GIRK2 and FOXA2 but strongly positive for calbindin ( Figure 1J). This distinct pattern of GIRK2/FOXA2/calbindin expression in the SNc and VTA is consistent with those reported in other species, including rodents and humans (15,28,29). We also evaluated the induction efficiency of MSC-DP cells by quantitative immunocytochemistry.…”
Section: Evaluation Of Msc-dp Cellssupporting
confidence: 87%
See 1 more Smart Citation
“…When control tissues obtained from a cynomolgus embryo and an adult animal were analyzed, both showed that the substantia nigra pars compacta (SNc) was strongly positive for GIRK2 and FOXA2 and weakly positive for calbindin, while the ventral tegmental area (VTA) was weakly positive for GIRK2 and FOXA2 but strongly positive for calbindin ( Figure 1J). This distinct pattern of GIRK2/FOXA2/calbindin expression in the SNc and VTA is consistent with those reported in other species, including rodents and humans (15,28,29). We also evaluated the induction efficiency of MSC-DP cells by quantitative immunocytochemistry.…”
Section: Evaluation Of Msc-dp Cellssupporting
confidence: 87%
“…We analyzed the relative expression levels of GIRK2, FOXA2, and CALB1 mRNAs using RT-PCR to classify MSC-DP cells as A9-type neurons (GIRK2 + /FOXA2 + /CALB1 − ) or A10-type neurons (GIRK2 − /FOXA2 − /CALB1 + ) (28,29,56). The amount of cDNA was normalized on the basis of the signal from the ubiquitously expressed β-actin.…”
Section: Evaluation Of Msc-dp Cells -Rt-pcrmentioning
confidence: 99%
“…Some midbrain DA neurons, especially those in the ventral tegmental area, contain CCK8 or calbindin [30,31]. Immunohistochemical analyses indicated that the TH + neurons generated after early FGF8 treatment were not labeled with calbindin, although calbindin-expressing neurons were observed (Fig.…”
Section: Da Neurons Produced With Fgf8 Treatment Before or After Sox1mentioning
confidence: 93%
“…Desde então, diversos autores tem caracterizado a substância negra, as definições e terminologias que incluem divisões e sub-regiões variam de autor para autor (Braak e Braak, 1986;Fearnley e Lees, 1991;Gibb e Lees, 1991; van Domburg e ten Donkelaar, 1991;McRitchie et al, 1995;McRitchie et al, 1996;Damier et al, 1999a;).…”
Section: Discussionunclassified
“…Utilizando uma combinação de fatores anatômicos e neuroquímicos, alguns autores definiram quatro regiões: parte medial (também referido como o grupo ventromedial), parte lateral (também conhecida como nigrosomes 3), dorsal (também referida como nigrosomes 4, 5 e a matriz) e ventral (também referida como nigrosomes 1 e 2) (McRitchie et al, 1996;Damier et al, 1999a).…”
Section: O Envelhecimento E a Doença De Parkinsonunclassified